Transcriptional analysis of the Staphylococcus aureus plasmid pI258 mercury resistance determinant. - Skinner, J S (1991)
Northern blot DNA-RNA hybridization analysis of Staphylococcus aureus cells bearing pI258 showed that upon induction the amount of mer operon transcript present increased 49-fold over that observed in uninduced cells. Maximum induction occurred after 45 min in the presence of 5 microM HgCl2. Two transcripts, 5.0 and 5.8 kb long, were observed. Both transcripts encoded merR through merB (inclusive). Primer extension analysis determined that the 5' end of at least one transcript (and presumably of both) started at a T or G, 7 or 8 nucleotides downstream from the putative -10 site.